Lithuanian Timber Economy - Morkevičius, Antanas (Ekonomika, 1995)
The article gives dexcription of the development of Lithuanian forestry sector, woodworking industry, domestic and foreign timber trade in 1970–1990 (till the restoration of Independence). During that period timber resources in the local forests had been increasing, wood processing industry has been under intensive modernization. In 1990 30% of the total territory were covered with forests, annual growth made 4,7 million m3. 45 thousand of employees were engaged in the harvesting works and the wood processing industry, total production of the industry exceeded 700 million roubles. In 1990 wood consumption per capita reached 1,06 m3 in Lithuania.